Stress concentration coefficients of a woven textile composite layer with local processing defects under pure forming conditions - Dedkov, Denis Vladimirovich; Tashkinov, Anatoliy Aleksandrovich (Computational Continuum Mechanics, 2013)
A new model has been developed to simulate a woven textile composite layer with a polycrystalline matrix. Based on the numerical solution of the boundary–value problem by the finite-element method, the values of stress concentration caused by local processing defects (break in a fiber, closed internal pore) in pure forming are obtained. It is shown that application of additional processing operations to fill the formed voids by matrix material can decrease stress concentration and increase the ability of a material to withstand external force loads. The mechanisms responsible for initiation of damages in a polycrystalline matrix are determined.